(untitled) - Thayne, RaeAnne (Toronto, Ontario, 2022)
"Secrets come to light as a town tries to heal in New York Times bestselling author RaeAnne Thaynes beloved Hopes Crossing series! Maura McKnight-Parker is still reeling from the loss of her youngest daughter when Jackson Lange, her first love, returns to Hopes Crossing. Everything is made all the more complicated when Sage, Mauras older daughter--the child Jackson never knew he had--returns home at the same time. Facing those he left behind for the first time in years, Jackson finds himself tentatively reaching out to his estranged father and thrown back together with Maura as he gets to know his daughter. But not all the mistakes from the past can be smoothed over so easily, and when Sage reveals secrets of her own, he and his newfound family will have to decide what theyre willing to do for love."--
Keywords: Fiction; Man-woman relationships; Fiction; Families; Fiction; Secrecy; Colorado; Fiction; Domestic fiction; Fiction; Romance fiction; Romance fiction; Domestic fiction; Novels